Safety and Efficacy of Trans-Radial Percutaneous Coronary Intervention – Experience in a Tertiary Level Hospital of Bangladesh - Shimu, Ishrat Jahan; Alam, Muhammad Badrul; Islam, AKM Monwarul; Asaduzzaman, Khondoker; Khan, Amiruzzaman; Khoda, Mohammad Mehfuz E (Cardiovascular Journal, 2020)
Background: Like elsewhere, there is an ongoing paradigm shift of route of vascular access for percutaneous coronary intervention (PCI) from trans-femoral to trans-radial in Bangladesh. However, the efficacy, safety and cost effectiveness of TRI in Bangladesh have not been studied adequately. The present study was carried out to find the safety and efficacy of trans-radial PCI in a tertiary level hospital of Bangladesh. Methods: The prospective observational study was conducted in the Department of Cardiology, Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), Dhaka over a period of 1 year from January to December 2016. A total of 90 subjects were included in the study. Of them, 45 patients had PCI through trans-femoral approach (group 1) and 45 through trans-radial approach (group 2). Results: The baseline characteristics were comparable except the gender distribution. Vascular access failure was more commonly encountered in trans-radial than in trans-femoral route (p = 0.0002). Angiographic success was comparable between the groups. Though not statistically significant, overall complications and per-procedural and post-procedural complications were more commonly encountered in trans-femoral than in trans-radial approach. In-stent thrombosis, arrhythmia and fever were insignificantly more common in trans-radial access whereas, puncture related complications, bleeding and death were more common in trans-femoral than the counterpart. Conclusion: Compared to trans-femoral PCI, trans-radial PCI has reasonable safety and efficacy. However, patients should be selected for TR-PCI more carefully to avoid vascular access failure. Cardiovasc. j. 2020; 13(1): 46-51